Impact of cardiopulmonary bypass duration on efficacy of fibrinogen replacement with cryoprecipitate compared with fibrinogen concentrate: a post hoc analysis of the Fibrinogen Replenishment in Surgery (FIBRES) randomised controlled trial. (September 2022) - Bartoszko, Justyna; Martinez-Perez, Selene; Callum, Jeannie; Karkouti, Keyvan; ,; Farouh, Michael E.; Scales, Damon C.; Heddle, Nancy M.; Crowther, Mark; Rao, Vivek; Hucke, Hans-Peter; Carroll, Jo; et al.
Abstract: Background: Coagulopathy in cardiac surgery is frequently associated with acquired hypofibrinogenaemia, which can be treated with either purified fibrinogen concentrate (FC) or cryoprecipitate. Because the latter is not purified and therefore contains additional coagulation factors, it is thought to be more effective for treatment of coagulopathy that occurs after prolonged cardiopulmonary bypass (CPB). We examined the impact of CPB duration on the efficacy of the two therapies in cardiac surgery. Methods: This was a post hoc analysis of the Fibrinogen Replenishment in Surgery (FIBRES) RCT comparing FC (4 g) to cryoprecipitate (10 U) in adult patients undergoing cardiac surgery and experiencing bleeding with acquired hypofibrinogenaemia ( n =735). The primary outcome was allogeneic blood products transfused within 24 h after CPB. Subjects were stratified by CPB duration (≤120, 121–180, and >180 min). The interaction of treatment assignment with CPB duration was tested. Results: Subjects with longer CPB duration experienced more bleeding and transfusion. With CPB time ≤120 min (FC, n =134; cryoprecipitate, n =146), the ratio of least-squares means between the FC and cryoprecipitate groups for total allogeneic blood products at 24 h was 0.90 (one-sided 97.5% confidence interval [CI]: 0.00–1.12); P =0.004. For subjects with CPB time 121–180 min, it was 1.00 ([one-sided 97.5% CI: 0.00–1.22]; P =0.03], and for CPB time >180 min it was 0.91 ([one-sided 97.5% CI: 0.00–1.12]; P =0.005). Results were similar for all secondary outcomes, with no interaction between treatment and CPB duration for all outcomes. Conclusions: The haemostatic efficacy of FC was non-inferior to cryoprecipitate irrespective of CPB duration in cardiac surgery. Clinical trial registration: NCT03037424 .